Impact of Hedonistic Lifestyle on Social Interaction among High School Students: A Case Study in Indonesia - Damanik, Nelly Syahfitri Br; Dora, Nuriza (Yayasan Ilomata, 2024)
This study aims to analyze the impact of hedonism lifestyle on students' social relationships at SMA Negeri 4 Binjai. The hedonism lifestyle, which focuses on the search for pleasure and instant gratification through the consumption of luxury goods and participation in high-cost social activities, has become an increasingly common phenomenon among teenagers. This research used a qualitative approach with an analytical descriptive method, involving observation, interviews and documentation of students, subject teachers, counseling teachers and school principals. The results showed that the hedonism lifestyle has a significant impact on the dynamics of students' social relationships. Students who follow this lifestyle tend to form exclusive social groups based on economic status, which triggers feelings of injustice and jealousy among students. The hedonistic lifestyle distracts students from academic achievement and other positive activities, reduces the quality of more meaningful interpersonal relationships, and increases excessive consumptive behavior. The study also found that family economic conditions, the influence of social media, and the role of peers are the main factors that encourage the adoption of a hedonistic lifestyle among students. To overcome this negative impact, the study recommends improving character education programs in schools, the active role of parents in teaching wise economic values, as well as students' efforts in developing awareness of time management and priorities.